Bloc politics and new political issues: Patterns of cooperation in the Danish parliament - Green-Pedersen, Christoffer; Skjæveland, Asbjørn (Politica, 2020)
The article starts out by discussing bloc politics in the Danish parliament, the Folketing, from 1973 until today. It investigates the parties’ legislative voting behavior in 2007-2017 and asks how differently parties are positioned on new and old politics and whether there is a different degree of bloc politics on these two issue areas. The article shows that no party from one block has moved in between parties from the other block on new or old politics. However, a one-dimensional perspective is challenged – at times substantially – by varying party positions within the two blocks. An analysis of the degree of bloc politics on new and old politics shows that there is no substantial difference in the degree of bloc politics on the two issue areas.